Resazurin microtitre plate assay and Sensititre® MycoTB for detection of Mycobacterium tuberculosis resistance in a high tuberculosis resistance setting - Prenika Jaglal; Melendhran Pillay; Koleka Mlisana (AOSIS, 2019)
Background: Rapid diagnosis of drug-resistant Mycobacterium tuberculosis is a challenge in low-income countries. Phenotypic drug susceptibility testing using Sensititre® MycoTB assay and the resazurin microtitre plate assay (REMA) are relatively new innovative methods to determine drug susceptibility. Objectives: This study aimed to determine the performance of the Sensititre and REMA for M. tuberculosis drug susceptibility testing in a high-volume tuberculosis reference laboratory. Methods: A laboratory-based study was performed at the Inkosi Albert Luthuli Central Hospital Tuberculosis Laboratory from January 2014 to June 2015. The Sensititre® MycoTB plate and REMA were compared to the gold standard agar proportion method (APM) using 134 stored isolates. Results: Agreement between the Sensititre® MycoTB plate and APM was observed with 98% sensitivity, 82% specificity, 94% positive and 93% negative predictive values of the Sensititre® MycoTB assay for the detection of rifampicin resistance and 97%, 96%, 99% and 88% for isoniazid resistance. Good categorical agreement between the REMA and the APM was observed among isolates with 89% sensitivity, 68% specificity, 89% positive and 68% negative predictive value for the detection of rifampicin resistance and 95%, 96%, 99% and 81% for isoniazid resistance. Results for the second-line drugs showed elevated minimum inhibitory concentrations for multidrug-resistant and extensively drug-resistant tuberculosis isolates. Conclusion: The REMA and Sensititre® MycoTB plate are attractive alternatives to the gold standard APM for the phenotypic detection of M. tuberculosis drug resistance.